The Relationship between Love of Money, Islamic Religiosity and Life Satisfaction: a Muslim’s Perspective - Arif - Hoetoro (Ekonomi Syariah IAIN Kudus, 2020)
This research scrutinizes the relationship between Love of Money (LOM), hedonic behavior and Islamic religiosity in pursuing life satisfaction in consumption. By utilizing accidental sampling method, the research then employed 99 customers who spent their money in one of the biggest department stores in Malang City. The calculation of data with SmartPLS-3.1.8 revealed that Islamic religiosity significantly affects live satisfaction (β = 0.290; ρ-value = 0.003). In the same time, LOM significantly influences hedonic behavior (β = 0.417; ρ-value = 0.000). However, hedonic behavior does not mediate the relationship between LOM and life satisfaction. This study accordingly concludes that Islamic religiosity plays a main role in consumption. Therefore, it is suggested that every Muslim have to instill Islamic religiosity in daily activities for obtaining life satisfaction.